New contributions to the taxonomy and phylogeny of the ciliate genus Pleuronema (Ciliophora, Scuticociliatia), with descriptions of two new species collected from the subtropical coastal wetlands in China - Wu, Zehao; Liu, Mingjian; Ye, Tingting; Zhao, Xuetong; Wu, Fan; Jiang, Yaohan; Chen, Xiangrui (Frontiers in Marine Science, 2023)
Ciliates of the genus Pleuronema are a speciose and ubiquitous group. Recent studies suggest that there may be a sizable amount of undiscovered species diversity. In the present study, two new Pleuronema species have been isolated from the subtropical coastal waters of China and characterized using morphological and taxonomical methods: Pleuronema pulchra n. sp. is characterized by a body size of 75–90 × 25–40 µm in vivo, 32–48 somatic kineties, four to seven preoral kineties, somatic kinety 1 composed of about 80 kinetids, and membranelle 2a with a single-rowed mid-portion and hook-like posterior portion. Pleuronema warreni n. sp. is defined by a body size of 55–80 × 25–45 µm in vivo, 35–42 somatic kineties, three to six preoral kineties, somatic kinety 1 with approximately 75 kinetids, and a mid-portion of membranelle 2a that is single-rowed and extremely long (occupying > 75% length of M2a). The phylogenetic analysis of the small subunit ribosomal RNA genes of Pleuronema members, including those of the two novel species, shows that the genus Pleuronema is a polyphyletic group. Both new species form a cluster with Pleuronema binucleatum KT033424, P. elegans KF840518, and “P. coronatum” JX310014 (identification to be verified). Additionally, we provide an illustrated key for 20 “coronatum-type” Pleuronema species, including the two new ones.